Protective effect of moringa seed extract on kidney damage in rats fed a high-fat and high-fructose diet - Indah S. Putri, MD; Gita N. Siwi, MD; Dyah R. Budiani, M.Si; Bastomy E. Rezkita, MD (Journal of Taibah University Medical Sciences, 2023)
المخلص: أهداف البحث: المورينجا نبات شائع يحتوي على مستويات عالية من مضادات الأكسدة. وبالتالي، تهدف هذه الدراسة إلى تحليل التأثير الوقائي لمستخلص بذوره على الكلى لنموذج الفئران مع نظام غذائي عالي الدهون وعالي الفركتوز. طريقة البحث: تم استخدام طريقة تصميم مجموعة التحكم قبل الاختبار وبعد الاختبار لقياس المعلمات الأيضية ووظائف الكلى ، بينما تم استخدام طريقة ما بعد الاختبار فقط في المجموعة الضابطة لتقييم الحجم الكبيبي وتعبير ديسموتازات الأكسيد الفائق. تم استخدام أخذ العينات الهادفة على 28 جرذا مقسمة إلى أربع مجموعات: مجموعة التحكم (ك1)، وثلاث مجموعات تغذت على نظام غذائي عالي الدهون وعالي الفركتوز لمدة 53 يوما (ك2 و ك3 وك4). بعد ذلك، تم إعطاء (ك3) 150 مجم / كجم من وزن الجسم / يوم؛ وتم إعطاء (ك4) 200 مجم / كجم من وزن الجسم / يوم مستخلص بذور المورينجا لمدة 28 يوما. النتائج: أظهرت النتائج أن النظام الغذائي يزيد من مخاطر الإصابة بمتلازمة التمثيل الغذائي المتمثلة في زيادة الوزن والجلوكوز والدهون الثلاثية. أدت الجرعة المثلى من إدارة مستخلص بذور المورينجا إلى تحسن كبير في الحجم الكبيبي. الاستنتاجات: أعطت إدارة مستخلص بذور المورينجا تأثيرا وقائيا على الكلى عن طريق خفض مستويات الكرياتينين في الدم ، وتحسين الهيكل العام ، وزيادة التعبير عن مضادات الأكسدة ديسموتازات الأكسيد الفائق. Abstract: Objective: Moringa is a common plant that contains high levels of antioxidants. In this study, we aimed to analyze the protective effect of moringa seed extract on the kidneys of a rat model maintained on a high-fat and high-fructose (HFHF) diet. Methods: An experiment with a pretest-posttest control group design was used to measure metabolic parameters and determine kidney function, while a posttest-only method was used for the control group to determine glomerular volume and superoxide dismutase (SOD) expression. Purposive sampling was used on 28 rats divided into four groups: a control (K1) group, and three groups fed a HFHF diet for 53 days (K2, K3, and K4). Subsequently, K3 and K4 were given 150 and 200 mg/kg BW per day moringa seed extract for 28 days. Data were analyzed using IBM® SPSS® Statistics version 22 software. Results: Analysis showed that the diet increased the risk of metabolic syndrome, as evidenced by weight gain, glucose, and triglycerides. The optimal dose of moringa seed extract significantly improved glomerular volume (p = 0.001). The expression of SOD in kidney tubules and glomeruli was significantly different with each group (p = 0.002 and p = 0.001) respectively. Conclusion: The administration of moringa seed extract provided a protective effect on the kidney by reducing serum creatinine levels, improving overall structure, and increasing the expression of SOD, a key antioxidant.